Morphological and morphometric variability in the zoea I larvae of Pugettia quadridens (De Haan, 1839): looking for reliable characters for taxonomic studies on the genus Pugettia Dana, 1851 (Majoidea: Epialtidae) - Tamura, Hiroaki; Landeira, José M.; Goshima, Seiji (Zootaxa, 2017)
The larval morphology of Pugettia quadridens (De Haan, 1839) has been described several times, but the lack of voucher specimens (both larvae and spent females), makes it impossible to verify whether the remarkable heterogeneity, which has been described by the different authors, are due to intra-specific variability. We re-described the morphological and morphometric features of the first zoeal stage of the species, depositing voucher specimens for future examination by the scientific community. We used four females that were collected in the same locality in Hakodate Bay, Japan, and found significant morphological and morphometric intra-specific variability, both within and among clutches. One important variation was the setal count on the endopod of maxilla (3–4, rarely 5), which have been considered in previous studies to be a key character to distinguish species within genus Pugettia Dana, 1851. The size differences were rather striking, and the mean carapace length of the largest clutch (0.73 ± 0.04 SD mm) was up to 0.1 mm larger than the smallest one (0.63 ± 0.02 mm). We establish herein a solid taxonomic background for further larval descriptions of species of Pugettia with reliable characters and recommend the use of different clutches to prevent insufficient morphological descriptions due to intra-specific variability.